ANALISIS PROGRAM NU PRENEUR DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Amrizal Amrizal; Solihin Solihin (Commodities, Journal of Economic and Business, 2024)
Zakat is the third pillar of Islam. The definition in the rules of syar`i is the level of the assets of course which must be issued by certainpeople to be given to the rightful according to the povisions of sara`. In terms of language, the word zakat has ameaning, namely ath-thaharatu`kesucian`, while in terms of, namely that zakat is part of a propety with certain conditions, which Alloh SWT requires for it owner, to behended over to those entirled to receive it, with certain requirements too. The Nganjuk branch of LAZISNU in the NU Preneur program, the is relly zakat chaneneneled is the best. Hhe zakat is relly to fokus. The objectives of thi study are: 1) Explain how zakat is maaged through the NU preneur program at the Nganjuk branch of LAZISNU. 2) What isthe role ofin LAZISNU OF the Nganjuk branch in improving community walfare. 3) Explain how the reults of zakat management through the NU Preneur program in the Nganjuk branch of LAZISNU. The research that the writing did included descriptif qualitative analysis, namely data analysis carried out by organizing and systematically analyzing all the data obtained. Descriptive research is researchthat uses an event, symptoms, events thet occur at the present time, meaning descriptive research is taking problems or focusing on actual problems as they ware at the research was carrid out. The results of this study, NU Preneur program is LAZISNU of the Nganjuk. the zakat is really channeled to mustahiq. really felt the impact of being moreeconomically empowered, becase it was able to meet the necessities of life for today, tomorrow and so on. The research is was able to Nganjuk branch LAZISNU and the writings.